Pengaruh Dukungan Orang Tua Terhadap Pendidikan Anak - Mawar Febrianti; Ariqah Salsabila; Muhammad Abrar Umar; A. Octamaya Tenri Awaru (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The research we conducted was to discuss in depth how the role of parental support can influence a child's education. Parental support has an influence that is considered important on a child's development and success. This research emphasizes the importance of open communication between humans, parents and children in dealing with educational problems. Through active involvement, guidance and emotional support, parents can help children develop social skills, responsibility and intrinsic motivation.